IMPROVING THE LEARNING MOTIVATION OF ELEMENTARY SCHOOL CHILDREN THROUGH TRADITIONAL GAMES IN FACING STAY–AT–HOME SITUATIONS - Muhardila Fauziah; Ade Eka Anggraini; Yeni Sulaeman; Lenni Marlina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The pandemic happened around the world has brought a major impact on the hfield of ealth and economy, as well as education. The government closed crowded places, offices, and schools. The school closures resulted in children in a situation called Stay At Home. The purpose of this research was to find out the efforts of parents and teachers in maintaining children's learning motivation at home, and the role of traditional games to increase children's learning motivation in facing Stay–At–Home situations. This research utilized a phenomenological approach with descriptive qualitative research. This research involved parents, teachers, and elementary school students in Solok. After approximately eight months, the schools as the research objects were closed so that students and teachers conducted learning from home. As a result, teachers, assisted by the guidance of parents, were demanded to create an active and creative atmosphere in teaching in order that students did not feel bored and learning objectives were achieved. One  of the efforts was to encourage the children to play around the house so that the child did not feel bored. Traditional games were an effective alternative to minimaze the influence of gadgets.